TIRES, OVERSIZE, SPECIAL AND DESERT. PHASE 3: SUBARCTIC EVALUATION - ARMY TRANSPORTATION BOARD FORT EUSTIS VA (1963)
An evaluation of special oversize tires mounted on cargo vehicles to determine the capability of tires of increased size to improve wheeled vehicle mobility in subarctic terrain and environment.